An ac impedance study of dendritic silver three-dimensional electrodeposits - Hernández-Creus, A. (1993)
The ac impedance behaviour of electrochemically grown dendritic Ag three-dimensional electrodeposits grown from aqueous Ag+ ion containing solutions has been studied in the blocking regime covering the 1 ⩽ f ⩽ 104 Hz frequency range (ω = 2πf). These deposits exhibit fractal surface and non fractal mass (volume) characteristics. Impedance data displayed as log Z″ vs. log ω plots show two linear portions with different frequency dispersion exponents <α > = 0.95 ± 0.03 and <α > = 0.67 ± 0.05, respectively. The crossover frequency, ωλ, as determined from those plots, mainly depends on the electrolyte resistivity and, to a minor extent, on the Ag+ ion electrodeposition charge. For ω > ωλ, the surface fractal dimension derived from the reciprocal relationship, Ds = (1/α) + 1, is Ds = 2.45 ± 0.1. This figure agrees with that obtained from the log (area) vs. log (volume) plots.